Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.3109/00498259209053154
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biodisposition and metabolism of14C-(±)-fenfluramine in mouse, rat, dog and man

Abstract: 1. The comparative metabolism of fenfluramine was investigated in mouse, rat, dog and man following a single oral dose of 14C-(+/-)-fenfluramine hydrochloride (1 mg/kg), and also in rat after eight consecutive 12-h subcutaneous doses (24 mg/kg). 2. Main route of excretion of radioactivity in all species and at all doses was into urine (> 80%), with only minor amounts of radioactivity found in faeces. 3. From all species examined a total of 11 metabolites were observed in urine and plasma by t.l.c. and h.p.l.c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…In the rat, recent studies have used selective 5-HT 1B and 5-HT 2C receptor antagonists and shown that 5-HT 1B receptor activation plays no role in the hypophagia induced by d-fenfluramine, or its metabolite d-norfenfluramine, whereas antagonism of 5-HT 2C receptors produced an almost complete reversal of the hypophagic effect of either drug (Vickers et al 2001a). However, there are significant differences in the metabolism of fenfluramine between rats and mice (Caccia et al 1982;Marchant et al 1992) that might predict a different pattern of results in the two species. In particular, the ratio of plasma d-fenfluramine to d-norfenfluramine is much higher in the mouse than in the rat.…”
Section: Discussionmentioning
confidence: 94%
“…In the rat, recent studies have used selective 5-HT 1B and 5-HT 2C receptor antagonists and shown that 5-HT 1B receptor activation plays no role in the hypophagia induced by d-fenfluramine, or its metabolite d-norfenfluramine, whereas antagonism of 5-HT 2C receptors produced an almost complete reversal of the hypophagic effect of either drug (Vickers et al 2001a). However, there are significant differences in the metabolism of fenfluramine between rats and mice (Caccia et al 1982;Marchant et al 1992) that might predict a different pattern of results in the two species. In particular, the ratio of plasma d-fenfluramine to d-norfenfluramine is much higher in the mouse than in the rat.…”
Section: Discussionmentioning
confidence: 94%
“…It could be partly related to the binding of fenfluramine in plasma (ϳ40%) (38). Also, the metabolism of fenfluramine is much faster in rats than in humans (22). There are data supporting species differences in the density of 5-HT receptors (19,35).…”
Section: Discussionmentioning
confidence: 99%
“…In humans and animals receiving systemic (±)-fenfluramine, circulating concentrations of (+)-and (−)-norfenfluramine are similar to or greater than concentrations of fenfluramine itself 25, 26. Moreover, stereoisomers of (±)-fenfluramine and (±) norfenfluramine cross the blood-brain barrier to accumulate in the central nervous system.…”
Section: Pharmacology Of Fenfluraminesmentioning
confidence: 99%